Evolution of MXene and its 2D heterostructure in electrochemical sensor applications - Ab. Latif, Farah Ezzah (Elsevier B.V., 2022)
The increasing environmental pollution and recurrent viral outbreaks have piqued researchers’ interest in experimenting with new materials to improve electrochemical sensing properties and develop rapid, sensitive, low-cost, environmentally friendly, real-time detection devices that could generate data beneficial for health and environmental monitoring. Due to their wide range of applications, transition metal carbides and nitrides (MXene) have recently gained prominence in two-dimensional (2D) nanomaterials. MXene is a promising material for developing next-generation sensing applications due to its outstanding electronic and surface properties. Despite its numerous positive attributes, MXene exhibits a high proclivity for intersheet aggregation, lowering its electrochemical performance. To address this persistent issue, researchers attempted to integrate MXene with other 2D nanomaterials, nanoparticles, enzymes, or 3D materials, forming a composite with synergistic effects for enhancing sensing performance. Although plenty of literature is available in the sensor field, there is still a dearth of research on the two-dimensional MXene heterostructure, notably in electrochemical sensing applications. Thus, the main aim of this review is to elaborate on the 2D MXene heterostructure in the electrochemical sensing field. This review summarises different 2D MXene synthesis techniques, MXene characteristics, and sensing performance to provide a framework for developing high-performance sensors.